Public health education: Policy and research training contributing to translational research - Fleming, M.; Parker, E.; MacDougall, C.; McLean, K.; Howat, Peter (Australian Network of Academic Public Health Institutions, 2010)
In recent years there has been increased international attention given to translating public health research into practice (and/ through policy). The term translational research however, has been defined and classified in various, often inconsistent, ways in the health research literature. Consistency in the use of terms and classifications related to translational research will lead to increased understanding of the translational research process and more effective efforts to move science into practice (Spoth et al., 2008). In the health context, translational research provides a process that goes beyond the concept of evidence-based practice. While an evidence-based practice model ensures that practice is informed by research knowledge, approaches and outcomes tend to be dominated by the needs and philosophies of research. In other words, as Brown Urban and Trochim (2009, p. 540) state, ‘it tends to be formed primarily from a researcher, not practitioner perspective and prioritises knowledge generation over practical problems, and precision and control over generalisability and diffusion’. In contrast, translational research proposes a system of research that is both bidirectional and dynamic in nature. Thus, the needs of workers in applied settings are reflected in research agendas, while research advances in turn influence policy and practice decisions. This case study highlights the three main focal points of the dynamic process of translational research—the role of research, policy, and education—by using three vignettes of work that has used translational research approaches or aimed to educate students to undertake or understand translational research, and it discusses Building public health workforce capacity in Australia 31 future challenges in this area. These case studies illustrate the need to advance an educational platform that will equip tomorrow’s researchers, practitioners, and policy makers to competently apply a translational research framework.